Defeating the Vigilance Decrement. Issue 2 (2nd July 2016) - Hancock, Peter A.; Volante, William G.; Szalma, James L.
Abstract : OCCUPATIONAL APPLICATIONS We tested the boundaries of Parasuraman's vigilance taxonomy to see how porous they are. The degree of porosity is especially informative in mitigating and eliminating the vigilance decrement. These results are relevant to every form of human operation in automated, semi-automated, and autonomous computer-mediated systems. TECHNICAL ABSTRACT Background : When vigilance was stultified, and threatened to become moribund, Parasuraman's vigilance taxonomy revivified the area of research. The taxonomic description features dichotomies across event rate and target comparison type to establish the boundaries of consistent monitoring degradation. This insight implicated resource theory as the causal explanation for the vigilance decrement, founded on the depleting attentional demands of increasing memory load. Despite its manifest value, taxonomic differentiations still require the fixation of constraints that continually have to be challenged and re-evaluated in light of emerging evidence. Such a challenge is erected here. Purpose : To re-examine and re-evaluate the fundamental vigilance taxonomy in order to provide methods to defeat the vigilance decrement, predominantly by design. Methods : Using synthetic integration of accrued knowledge since its original inception down to the present time, our work evaluates and explicates limits to the boundaries represented in the classic vigilance taxonomy. This synthesis serves as a precursor to identifying ways to mitigate or eliminate the vigilance decrement. Results : The thresholds that connote the taxonomic limits are shown to be frangible and the very natures of their identified dis-continuities are themselves informative for methods of remediation. Conclusions : These results are relevant to every form of human operation in automated, semi-automated, and autonomous computer-mediated systems.